Ethical design intelligence : the virtuous designer - D'Anjou, Philippe (2020)
"Ethical Design Intelligence: The Virtuous Designer explores the deep significance of philosophy and ethics to the practice of design. It offers designers from disciplines such as architecture, urban design, planning, landscape, interiors, and industrial design an alternative ethical framework to expand their thinking about their practice. Arguing that design today is primarily an agency driven by the momentum of globalisation, embedded in economy, materialism, and utility, the book reconceptualizes the notion of virtue in design practice. Across chapters covering topics such as virtuous character, creative agency, and unsustainable practices, the book scrutinizes design through a philosophical lens. d'Anjou dissects articulations from different philosophical thinkers from antiquity to our contemporary time to reveal that ethics is fundamental to everything affected by design. Countering well-established modes of postmodern relativism in design, which has led to defuturing and unsustainability, ethical realism is presented as an alternative solution. Written for designers, educators, researchers, and students"--
Includes bibliographical references and index.
Keywords: Design -- Moral and ethical aspects